Advancing Agro-Based Research - New Straits Times, Mohd Noor Aswad (2008)
Taking the next step sums up Universiti Putra Malaysia's (UPM) approach to research. The university now aims to create an environment that inspires innovative research following its selection as a research university by the Higher Education Ministry in November 2006.